Inventarisasi dan Intensitas Serangan Hama pada Tanaman Lemon (Citrus Limon L.) di PT. Al Fatih Porang Indonesia - Neneng Sholeha Diab; Rifni Nikmat Syarifuddin; Fenny Hasanuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Lemon (Citrus limon) is a fruit that is very popular with Indonesian people, with a fresh taste, contains vitamin C and has high marketability and economic value. Efforts to increase production cannot be separated from the problem of plant pests (OPT) in lemon plants, so it is necessary to seriously handle the pest problem. This research aims to determine the types of pests that attack lemon plants and the intensity of pest attacks on lemon plants at PT. Al Fatih Porang Indonesia. The research was conducted using a survey method with a population of 1,020 citrus plants that had reached the generative phase and the sample used was 51 plants (5% of the total population in accordance with Yount's theory, 1999) and each sample consisted of 4 sub-samples based on cardinal directions, so that the total the research unit was 204. The sampling pattern used a diagonal line pattern with a distance between sample plants of ± 6 m. The research procedure that will be carried out in this research is a pest inventory which is carried out in three stages, namely direct observation of sample plants, collecting insect pests found, and identification of the results of the collection in the laboratory. Observations were made on plant damage caused by pests in each sample unit by determining four branches as sample sub-units. The branches selected were branches that headed north, south, east and west by observing from the tip of the branch to all parts of the sample sub-unit (leaves, fruit, twigs). Apart from that, the main stem is also observed to see whether there is a stem borer attack or not. The damage observed was recorded in a table, then the presentation was calculated and the pests on the sample sub-unit branches and stems were collected and labeled, then identified in the laboratory with the help of the book Borror et al. (1992) and the book Key to Insect Determination translated by Achmad Sulthoni, et al. (1991). The output of this research is the final research report and scientific article with Accepted status in the Sinta 4 accredited journal.